Improving speaking ability of the students of SMK Kelautan dan Perikanan Negeri 12 Medan Labuhan by implementing role play technique - Iriance Iriance (English, 2018)
This research aims to describe whether role play technique can improve speaking ability of students of SMK Kelautan dan Perikanan Negeri 12 Medan Labuhan. The object of this research is 30 students of class XI and used as sample. This research was conducted in two cycles collaboratively where the researcher was assisted by English teacher as a collaborator. The implementation procedure of this research consists of four stagesincluding planning, implementation, observation, and reflection. Data were collected using several research instruments, viz. scoring rubric, observation sheet and field notes. The results show that role play is an effective learning technique in teaching speaking. Students can speak with confidence, use better grammar and pronounciation as well as increased vocabulary. Students become more active and enthusiastic, teaching and learning process becomes more interesting.